2015
DOI: 10.1371/journal.pone.0132669
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Epstein-Barr Virus Load: An Efficient Supplementary Method for Population-Based Nasopharyngeal Carcinoma Screening

Abstract: Serological detection of Epstein-Barr virus (EBV) antibodies is frequently used in nasopharyngeal carcinoma (NPC) mass screening. However, the large number of seropositive subjects who require close follow-up is still a big burden. The present study aimed to detect the nasopharyngeal EBV load in a high-risk population seropositive for antibodies against EBV, as well as to examine whether assay for nasopharyngeal EBV DNA load might reduce the number of high-risk subjects for follow-up and improve early detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 27 publications
(28 reference statements)
3
41
0
Order By: Relevance
“…Furthermore, changes in brush EBV DNA levels directly reflect the tumor response to treatment and can be used to identify local recurrent disease . Our data confirm and extend previous studies revealing highly elevated EBV loads in NP swabs or brushings from NPC‐patients as compared to controls . We found that the number of viral genomes per cell as well as the pattern of overall EBV latent and lytic gene expression profiles are comparable in parallel brush‐biopsy specimens, confirming the diagnostic value of NP‐brushings …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, changes in brush EBV DNA levels directly reflect the tumor response to treatment and can be used to identify local recurrent disease . Our data confirm and extend previous studies revealing highly elevated EBV loads in NP swabs or brushings from NPC‐patients as compared to controls . We found that the number of viral genomes per cell as well as the pattern of overall EBV latent and lytic gene expression profiles are comparable in parallel brush‐biopsy specimens, confirming the diagnostic value of NP‐brushings …”
Section: Discussionsupporting
confidence: 88%
“…The NP brushing has been proposed as an alternative for the invasive and painful biopsy in detecting the presence of NPC at the primary site of tumor development . NP brushings collected from NPC patients carry high levels of EBV DNA and carcinoma‐specific BARF1 mRNA reflecting the presence of viable tumor cells in the NP epithelium (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional MRI scanning may be helpful to depict subclinical cancers missed at endoscopy (34). However, these techniques are either invasive or expensive and, most importantly, cannot be performed by general physicians; thus, they are not suitable for mass screening programs, especially in rural areas where only limited health care facilities are available (18). The analysis of the diagnostic performance of the risk model in VCA-IgA-negative and -positive groups showed that 82.6% of VCA-IgA-negative patients with nasopharyngeal carcinoma in our study had positive Anti-EBV EUROLINE panel results (with cutoff value of 26.13%); whereas 83.3% of VCA-IgA-positive healthy people had negative Anti-EBV EUROLINE panel results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity and specificity were not satisfactory (16)(17)(18)). Hsu's research found that the sensitivity and specificity of VCA-IgA by ELISA in Chinese patients were 91.9% and 83.8%, respectively, compared with EBNA-1 IgA with sensitivity and specificity values of 80.0% and 80.0%, respectively (19).…”
Section: Introductionmentioning
confidence: 99%